O retrato de Augusto: poder, corpo e mito - Fernandes, Mayara Amaral [UNIFESP] (2016)
This work approachs the portrait of Augustan age, the most importante between the roman imperators, besides having the longest government. He gathers himself the functions of Emperor, Prince and Pontiff. Augustus could begin something new, adopting a consciously thought pictorial language to ensure your government and as a way to change the preconceived ideas of the population. The whole art production was testimony of the power and authority of the emperor. That being said, the central question of this work is: how did Augustus use your portraits in his political program? Thus, the approach is on the use of the art to express three themes: the representation of power, the status of the ruler by body reproductions and the legitimation of his domain through the myths. Giventhe many approaches currently practiced in the History of Roman Art, I have chosen one called "Art and Context", which puts its focus on production, function and reception of artistic works. Through the corpus, estabilished from the bibliography, analyses were made based on rulers portrait types, on circulation and transfer of ideals, models, artists and techniques between Greece and Rome, beyond the three main themes: power, body and myth. From that and bibliography it was made the argumentation about the conscious use of Augustan portraits types as way to achieve specific purposes and audiences.